Analisis Akurasi Geolokasi Smartphone di Ruang Terbuka dan Tertutup - Muhammad Arfah Asis; Muh Aliyazid Mude; St Nadya Kurnia Prihandani; Ririn Astiani (Universitas Islam Raden Rahmat, Malang, 2024)
Geolocation accuracy on smartphones is now a crucial factor in user experience, especially in location-based applications such as navigation and other location-based services. This research aims to analyze geolocation accuracy indoor and outdoor on two smartphones that have different signal frequencies. The method used is a comparative method that compares the results of four different scenarios. Geolocation accuracy measurements were carried out using the GPS Test application. The research results show that geolocation accuracy outdoors is higher when the smartphone location is still, while indoor, geolocation accuracy is better when the smartphone location is moving. Of the four scenarios tested, comparing accuracy between the first and second devices was only significant in the scenario where the smartphone was in a closed room. The first device shows an accuracy rate of 58.65% higher than the second device.